2022
DOI: 10.17305/bjbms.2022.8214
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of infraclavicular block success using the perfusion index: a randomized clinical trial

Abstract: The results of the pinprick and cold tests performed on the arm, forearm, and wrist-wrist areas of patients scheduled for upper extremity procedures are subjective and dependent on patient's compliance. The purpose of this study was to determine whether the perfusion index (PI) could be used as an objective indicator to demonstrate block efficacy. Fifty patients between the ages of 18 and 65 years who were scheduled for upper extremity procedures and had an American Society of Anesthesiologists risk assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Several researchers investigated the role of PI value in anesthesia management [ 13 ]. Seyhanlı et al analyzed the efficacy of infraclavicular block using PI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers investigated the role of PI value in anesthesia management [ 13 ]. Seyhanlı et al analyzed the efficacy of infraclavicular block using PI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the patients were aged between 18 and 65. This study concluded that the PI value was a valuable and sensitive parameter compared with conventional methods such as the pinprick test and Modified Bromage Scale [ 13 ].…”
Section: Discussionmentioning
confidence: 99%